Influence of initial (residual) stresses on the contact interaction of an elastic cylindrical punch and the elastic layer - Iaretska, N.A. (Reports of the National Academy of Sciences of Ukraine, 2014)
The article deals with the coaxial type problem of the pressure of an elastic cylinder on the layer with initial stresses within the linearized theory of elasticity. In general, the research was carried out for the theory of finite (large) deformations and two versions of the theory of small initial deformations with the elastic potential having an arbitrary form.